Effect of the fractions of Erythrina stricta leaf extract on serum urate levels and Xo/Xdh activities in oxonate-induced hyperuricaemic mice - Remya Raju, Sigimol Joseph, Soniya Scria, Santhosh M Mathews, M. Umamheshwari (Journal of Applied Pharmaceutical Science)
The present study was aimed at investigating the in vivo hypouricaemic activity of the various fractions of the hydromethanolic extract of the leaves of Erythrina stricta roxb (papilionacea) using oxonate-induced hyperuricaemic mice. The leaves of this species was used in traditional medicinal system for the treatment of gout, rheumatism, jaundice, bronchitis, fever, skin eruptions, wounds, etc. The pet-ether, chloroform, ethyl acetate and residual fractions at a dose of 200 mg/kg b.w. orally, were tested for their ability to reduce the serum urate level and inhibitory actions on the XO/XDH enzyme activities in the mouse liver and intestine. Potassium oxonate (280 mg/kg, i.p.), an uricase inhibitor was used to induce hyperuricaemia. Allopurinol (10 mg/kg, p.o.) was used as the positive control. The pet-ether, chloroform and ethyl acetate fractions when administered to hyperuricaemic mice produced a significant reduction in serum urate levels. In addition, these fractions elicited significant inhibitory actions on the XO/XDH enzyme activities in the mouse liver. The hypouricaemic activity may be due to the inhibition of XO/XDH enzymes. The effect of the fractions was less potent than allopurinol. The activity produced by the residual fraction was insignificant (P>0.05). Phytochemical screening of the leaves of Erythrina stricta revealed the presence of tannins, flavonoids, alkaloids and terpenoids. The presence of phytochemical constituents may be partly responsible for the beneficial effect of the fractions on hyperuricaemia and gout. These results suggest that the leaves of Erythrina stricta could be used as a potential source to treat gout and other inflammatory disorders.
Keywords: Erythrina stricta, gout, hyperuricaemia, uric acid, XO/XDH.